Financial Knowledge, Internal Control Locus, and Personal Money-Related Behavior: A Survey on Undergraduate Accounting Students - Sinta Setiana; Bram Hadianto (Integrated Journal of Business and Economics (IJBE), 2022)
This research intends to examine the impact of financial knowledge and internal control locus on student behavior to manage money and the effect of internal control locus on this knowledge. The students becoming the population are from the active undergraduate accounting department in Maranatha Christian University, distributed into six batches: 2015 to 2020; the number is 413. Considering this feature, we use the stratified random sampling method, setting the batches as the strata. After surveying the 200 students as the samples, the number of responded students is 193; hence, the participation level is 96.50%. Based on this situation, we use the structural equation model based on covariance after the validity and reliability tests are met. To sum up, this research unveils that money-related understanding does not affect student behavior. On the other hand, the internal control locus positively affects personal money-related behavior and financial knowledge.